Patient satisfaction with preoperative nursing care and its associated factors in surgical procedures, 2023: a cross-sectional study - Bizuayehu Atinafu Ataro; Temesgen Geta; Eshetu Elfios Endirias; Christian Kebede Gadabo; Getachew Nigussie Bolado (BMC, 2024)
Abstract Background To enhance patient satisfaction, nurses engaged in preoperative care must possess a comprehensive understanding of the most up-to-date evidence. However, there is a notable dearth of relevant information regarding the current status of preoperative care satisfaction and its impact, despite a significant rise in the number of patients seeking surgical intervention with complex medical requirements. Objective To assess patient satisfaction with preoperative nursing care and its associated factors in surgical procedures of, 2023. Methods A cross-sectional study was conducted, and the data was collected from the randomly selected 468 patients who had undergone surgery during the study period. The collected data was entered into Epidata version 3.1 and analyzed using SPSS version 25 software. Results The complete participation and response of 468 participants resulted in a response rate of 100%. Overall patient satisfaction with preoperative nursing care was 79.5%. Sex (Adjusted odds ratio (AOR): 1.14 (95% confidence interval (CI): 0.21-2.91)), payment status for treatment (AOR: 1.45 (95% CI: 0.66-2.97)), preoperative fear and anxiety (AOR: 1.01, 95% CI: 0.49-2.13)), patient expectations (AOR: 3.39, 95% CI: 2.17-7.11)), and preoperative education (AOR: 1.148, 95% CI: 0.54-2.86)) exhibited significant associations with patient satisfaction with preoperative nursing care. Conclusion It is important to exercise caution when interpreting the level of preoperative nursing care satisfaction in this study. The significance of preoperative nursing care satisfaction lies in its reflection of healthcare quality, as even minor deficiencies in preoperative care can potentially lead to life-threatening complications, including mortality. Therefore, prioritizing the improvement of healthcare quality is essential to enhance patient satisfaction.